(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In this article, pedagogical and psychological features of diagnosing preschool children’s readiness to study at school are highlighted, as well as the issues of formation and development of children’s motivation to study in the framework of effective use of practical research in a creative direction.